Rediscovery and revised description of Thismia bifida (Dioscoreales, Thismiaceae) - Dančák, Martin; Hroneš, Michal; Sochor, Michal; Uvírová, Alena; Blažek, Vojtěch Tobias; Jaafar, Salwana; Yiing, Ling Chea; Pandai, Azlan; Sukri, Rahayu Sukmaria (Phytotaxa, 2026)
Thismia bifida was described in 1967 from a single collection made in 1963 on Bukit Kana, Sarawak, Malaysia, and had not been recollected since, leaving uncertainties about its identity and affinities. We report the rediscovery of T. bifida at its type locality and document several additional populations across Sarawak and Brunei Darussalam. Based on detailed morphological examination of living material and molecular phylogenetic analysis of nuclear and mitochondrial loci, we provide a comprehensive revised description and notes on its phylogenetic relationships. The species exhibits considerable variability in flower size, colouration, length of tepal appendages, length of supraconnective appendages, and shape of stigma lobes. Our findings demonstrate that T. bifida is rather widespread, occurring in both lowland and montane forests. Phylogenetic reconstruction reveals that T. bifida is closely related to T. pallida from Sabah and T. filiformis from Thailand, together forming a well-supported clade (the Thismia filiformis group) within Thismia sect. Thismia subsect. Odoardoa. These observations clarify the taxonomic boundaries between T. bifida, T. filiformis, and T. pallida, and highlight the importance of revisiting historical localities of poorly known mycoheterotrophic taxa.